UTILIZATION OF DIGITAL MEDIA FOR ISLAMIC RELIGIOUS EDUCATION LEARNING BASED ON DIGITAL INTELLIGENCE (CERDIG) AT SMPI DARUNNIYAHJETIS - Irman Maulana; Ainul Yaqin; Muhammad Ali Rohmad (RADJA PUBLIKA, 2025)
This study aims to develop and evaluate the effectiveness of digital learning media based on the Cerdig application in Islamic Religious Education (PAI) at SMPI Darunniyah Mojokerto. The media development method, through the stages of needs analysis, design, development, implementation, and evaluation, was carried out on students in grades VII to IX during the even semester of the 2024/2025 academic year. The results showed that the Cerdig learning media was able to significantly increase student interest and learning activities with the support of interactive features such as video, audio, quizzes, and discussion forums. Teachers and students responded positively to the use of this media, despite technical constraints such as limited internet network access and teacher skills in operating the application. This media has proven valid, practical, and effective in supporting PAI learning, while strengthening communication and collaboration between teachers and students. Teacher training and digital infrastructure support are key factors in ensuring the success of this application. This study recommends the development of more responsive features and the integration of Islamic character values ​​​​to optimize digital-based learning and make it more relevant to students' needs.